Low‐Cost, High‐Efficiency, and Efficiency Predictable Small Molecule Organic Dyes with Bis(4‐styryl)phenyl Amino Donor for Dye‐Sensitized Solar Cells. Issue 6 (18th March 2019) - Ying, Xintong; Liu, Yifei; Ling, Li; Xu, Mengchen; Bao, Benzhou; Bao, Xin; Pang, Aiying; Shao, Guang; Zhang, Yingjun; Fang, Jing‐Kun
Abstract : Three small molecule organic dyes (SMODs) with bis(4‐styryl)phenyl amino (BSPA) donorFWD4 ∼FWD6 are synthesized easily and applied as sensitizers for dye‐sensitized solar cells (DSSCs). The dipole moments ( µ ) ofFWD4∼FWD6 are calculated by using density functional theory (DFT) to be 7.49, 9.64, and 9.22 D, respectively. The DSSCs based onFWD4 ∼FWD6 exhibit high power conversion efficiencies ( η ) of 5.83%, 7.62%, and 7.39%, respectively. The linear regression equation η = 0.817 µ –0.370 is created with R 2 = 0.999 that reveals the equation owned high accuracy. Highly reliable linear equations are also obtained under different fabrication conditions, which indicates that the power conversion efficiency tendency is influenced only by these dyes' intrinsic property, the dipole moment. The excellent linear correlation between the dipole moment and power conversion efficiency indicates that it is very likely to predict the power conversion efficiency precisely by calculating the dipole moment, which gives a convenient way to connect the experimental results with theoretical calculations for dyes with similar molecular structures. Abstract : The linear regression equation η = 0.817 µ –0.370 ( R 2 = 0.999) is created according to the dipole moment and power conversion efficiency of three novel low cost small molecule organic dyes (SMODs, ca. 600 Da). A facile way is found to predict the power conversion efficiency by calculating the dipole moment for dyes with similar molecular structures.